Self-Incompatibility-Induced Programmed Cell Death in Field Poppy Pollen Involves Dramatic Acidification of the Incompatible Pollen Tube Cytosol. Issue 3 (28th January 2015) - Wilkins, Katie A.; Bosch, Maurice; Haque, Tamanna; Teng, Nianjun; Poulter, Natalie S.; Franklin-Tong, Vernonica E.
Abstract : Self-incompatibility triggers rapid cytosolic acidification that is necessary and sufficient for programmed cell death and pivotal in reorganizing F-actin and associated proteins within punctate foci. Abstract: Self-incompatibility (SI ) is an important genetically controlled mechanism to prevent inbreeding in higher plants. SI involves highly specific interactions during pollination, resulting in the rejection of incompatible (self) pollen. Programmed cell death (PCD ) is an important mechanism for destroying cells in a precisely regulated manner. SI in field poppy ( Papaver rhoeas ) triggers PCD in incompatible pollen. During SI -induced PCD, we previously observed a major acidification of the pollen cytosol. Here, we present measurements of temporal alterations in cytosolic pH ([pH]cyt ); they were surprisingly rapid, reaching pH 6.4 within 10 min of SI induction and stabilizing by 60 min at pH 5.5. By manipulating the [pH]cyt of the pollen tubes in vivo, we show that [pH]cyt acidification is an integral and essential event for SI -induced PCD . Here, we provide evidence showing the physiological relevance of the cytosolic acidification and identify key targets of this major physiological alteration. A small drop in [pH]cyt inhibits the activity of a soluble inorganic pyrophosphatase required for pollen tube growth. We also show that [pH]cyt acidification is necessary and sufficient for triggering several key hallmark features of the SI PCD signaling pathway, notably activation of a DEVDase/caspase-3-like activity and formation of SI -induced punctate actin foci. Importantly, the actin binding proteins Cyclase-Associated Protein and Actin-Depolymerizing Factor are identified as key downstream targets. Thus, we have shown the biological relevance of an extreme but physiologically relevant alteration in [pH]cyt and its effect on several components in the context of SI -induced events and PCD .